Factors associated with the absence of Brazilians in specialized dental centers - Inara Pereira da Cunha; Valéria Rodrigues de Lacerda; Gabriela da Silveira Gaspar; Edson Hilan Gomes de Lucena; Fábio Luiz Mialhe; Paulo Sávio Angeiras de Goes; Hazelelponi Querã Naumann Cerqueira Leite; Rafael Aiello Bomfim (BMC, 2022)
Abstract Aim To identify the individual and contextual factors associated with the absence of Brazilians at a scheduled appointment in Dental Specialties Centers (DSC). Methods This cross-sectional design uses the National Program for Improving Access and Quality of Dental Specialties Centers database, 2018. The outcome was the users' lack of at least one of the scheduled appointments. Contextual and individual independent variables were used, considering Andersen's behavioural model. The analyses were performed with the R Core Team and SAS (Studio 3.8, Institute Inc, North Carolina, U.S, 2019) programs. Results Of the 10,391 patients interviewed, 27.7% missed at least one of the consultations. In the adjusted multivariate model, the interpretation based on the effect size and 95% CI showed that the behaviour individual predisposing factors such as age ≤ 42 years (OR = 1.10; 95%CI:1.01-1.21), individual need factors such as participation in the "Bolsa Família" program (OR = 1,14; 95%CI:1.02-1.27), not being covered by the Family Health Strategy (OR = 1.15; 95% CI:1.02-1.30), and users of periodontics services (OR = 1.22;95%CI:1.05-1.40) were associated with absences. The behavioural factor associated with the outcome was that the DSC facilities were not in good condition (OR = 1.18; 95%CI:1.03-1.34). DSC located in the capital (OR = 1.12; 95% CI: 0.92-1.48) were 12% more likely to have dental absences than those in the interior region. Conclusion There are individual and contextual barriers associated with patients not attending specialised public dental consultations. DSC should offer adequate hours to patients, especially young adults and vulnerable people.